Fault tolerant multiwavelength optical rings with limited wavelength conversion. - Gerstel, O. (IEEE Journal on selected areas in communications)
This paper presents methods for recovering from channel failures, link failures, and node failures in wavelength-division multiplexed (WDM) point-to-point links and ring networks with limited wavelength conversion/switching capabilities at the nodes. Different recovery schemes are presented to handle each type of failure. Each scheme is evaluated based on the network hardware configuration required to support it and the performance and management overheads associated with fault recovery. Although similar recovery techniques have been used in conventional networks such as SONET, the constraints due to limited wavelength conversion require new and more complex solutions